2020
DOI: 10.3390/ijerph17165662
|View full text |Cite
|
Sign up to set email alerts
|

Association between Allergic Rhinitis and Regular Physical Activity in Adults: A Nationwide Cross-Sectional Study

Abstract: Evidence regarding the association between allergic rhinitis (AR) and physical activity (PA) is conflicting. Previous studies have mostly relied only on self-reported symptoms to define AR, did not classify AR by severity or persistence, and included only children or athletes. The present cross-sectional study evaluated the association between PA and objectively-defined AR and its subtypes in the general adult population using data for 1932 eligible participants aged 19 years or older in the 2010 Korea Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“… 44 , 45 , 46 Another study diagnosing AR using clinical symptoms in conjunction with an objective test of atopy found that vigorous physical activity increased the likelihood of severe and intermittent AR, and worsened rhinorrhea symptoms. 47 However, moderate-intensity exercise was found to decrease pro-inflammatory cytokine levels and improve AR symptoms. 48 Overall, while the association between physical activity and AR severity in AR cases remains to be further elucidated, the protective effect of physical activity against AR presentation appears to be consistent between studies.…”
Section: Discussionmentioning
confidence: 99%
“… 44 , 45 , 46 Another study diagnosing AR using clinical symptoms in conjunction with an objective test of atopy found that vigorous physical activity increased the likelihood of severe and intermittent AR, and worsened rhinorrhea symptoms. 47 However, moderate-intensity exercise was found to decrease pro-inflammatory cytokine levels and improve AR symptoms. 48 Overall, while the association between physical activity and AR severity in AR cases remains to be further elucidated, the protective effect of physical activity against AR presentation appears to be consistent between studies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for decreased MVPA and increased SB was that adolescents who were diagnosed with allergic respiratory diseases might have concerns about exacerbations of their diseases while participating in PA. Although adolescents with allergic respiratory diseases are reluctant to participate in PA, it is important to know that PA or exercise is not a risk factor for asthma and participating in vigorous PA positively affected individuals with allergic respiratory disorders [ 43 , 44 ]. In addition, one of the studies also found that individuals who participated in regular PA (i.e., MVPA) do not worsen the allergic rhinitis symptoms [ 45 ] and factors such as regular participation in MVPA are important to consider because it improves their pulmonary function [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason may due to the effect of physical activity on the induction and exacerbation of the allergic symptoms [ 48 ]. Another Korea research also proved that regular vigorous PA (physical activity) may aggravate AR (allergic rhinitis) symptoms by subjective or objective factors [ 49 ]. But there are different opinions and results.…”
Section: Discussionmentioning
confidence: 99%